Assessment and optimization of the fast inertial relaxation engine (FIRE) for energy minimization in atomistic simulations and its implementation in LAMMPS - Guénolé, Julien; Nöhring, Wolfram G.; Vaid, Aviral; Houlle, Frederic; Xie, Zhuocheng; Prakash, Aruna; Bitzek, Erik (Computational Materials Science, 2020)
In atomistic simulations, pseudo-dynamical relaxation schemes often exhibit better performance and accuracy in finding local minima than line-search-based descent algorithms like steepest descent or conjugate gradient. Here, an improved version of the fast inertial relaxation engine (FIRE ) and its implementation within the open-source atomistic simulation code LAMMPS is presented. It is shown that the correct choice of time integration scheme and minimization parameters is crucial for the performance of FIRE.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Atomistic simulation; FIRE; IMD; LAMMPS; Pseudo-dynamics; Relaxation

Atomistic Simulations of Compression Tests on gamma-Precipitate Containing Ni3Al Nanocubes - Houlle, Frederic; Walsh, Flynn; Prakash, Aruna; Bitzek, Erik (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2018)
The influence of gamma precipitates on the deformation behavior of gamma' Ni3Al nanocubes with 100 side surfaces is investigated by molecular dynamics simulations of uniaxial compression tests at 300 K. The plastic deformation of the nanocubes is caused by the nucleation of Shockley partial dislocations near the cube corners followed by the formation of pseudo-twins. While the dominant deformation mechanisms and the flow stress are not affected by the presence of precipitates, the precipitates reduce the yield stress by up to 10 pct and determine the location of dislocation nucleation. These findings can be rationalized by accounting for the misfit stresses caused by the presence of the gamma precipitates. Within the simulated ranges, the results are independent of cube size, rounding of the cube or precipitate corners, surface roughness, and strain rate. The observed precipitate softening in the dislocation-nucleation-controlled deformation of gamma' NiAl nanocubes is in stark contrast to the strengthening effect caused by the presence of a gamma phase in the gamma' precipitates in the microstructure of typical Ni- and Co-based superalloys.

Combining Experiments and Atom Probe Tomography-Informed Simulations on γ′ Precipitation Strengthening in the Polycrystalline Ni-Base Superalloy A718Plus - Kirchmayer, Andreas; Lyu, Hao; Pröbstle, Martin; Houlle, Frederic; Förner, Andreas; Huenert, Daniela; Göken, Mathias; Felfer, Peter; Bitzek, Erik; Neumeier, Steffen (Advanced Engineering Materials, 2020)
The strength of superalloys is strongly influenced by γ′ precipitates, whose size and volume fraction which can be adjusted by heat treatments. According to classical precipitation strengthening models, an increasing precipitate diameter should lead to a transition from weak to strong coupling of the dislocation pairs that form superdislocations in the γ′ phase. We show that long-term annealing of the Ni-base superalloy A718Plus at 670 and 680 °C increases the alloy's strength without significantly changing the grain size and η fraction. To understand the effect of the slight increase in γ′ size, detailed atom probe tomography (APT) was performed. Here, different field evaporation rates of the phases strongly affect the determination of the volume fraction when using the usual isosurface construction. This can be mitigated by considering the number density of atoms inside and outside the γ′ precipitates. Using an approximation of the precipitate shapes and arrangements from the APT data in atomistic simulations revealed that precipitate shearing by both, weakly and strongly coupled dislocations can occur in the same sample due to the wide distribution of precipitate sizes. These results highlight the need for advanced strengthening models that take into account the γ′ size distribution.
CRIS-Team Scopus Importer:2020-06-02
Keywords: atom probe tomography; atomistic simulations; Ni-base superalloys; precipitation strengthening; weak–strong pair coupling